Adaptation of Potato Varieties of Hungary to the Certain Conditions - Polgar, Zsolt; Тashmatova, М. А.; Kholdarov, М. U.; Lapasov, S. S.; Аripova, Sh. R.; Тursunov, D.; Ismoyilov, О. (Researchparks Publishing, 2023)
According to the cooperation agreement between the